2014
DOI: 10.5335/rfo.v19i2.3777
|View full text |Cite
|
Sign up to set email alerts
|

Ulotomia: coadjuvante do tratamento da má oclusão

Abstract: IntroduçãoA erupção dentária é o processo fisiológico que, durante a formação do dente migra, da posição intra--óssea até uma posição funcional na cavidade oral 1 . Vários fatores, sistêmicos e locais, podem, com o tempo, interferir na sequência de erupção dos dentes permanentes, dentre os fatores sistêmicos são apontados o hipopituitarismo, o hipotireoidismo e a disostose cleidocraneana; e como fatores locais destacam-se a retenção prolongada do elemento dentário, a perda precoce ou o trauma nos dentes decídu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 1 publication
0
3
0
8
Order By: Relevance
“…In cases of delay in the eruption of a dental element, clinical and complementary examinations must be carried out carefully to plan and perform the treatment efficiently 26 . In the present study, ulectomy in the region of tooth #21 was indicated, considering that from the Nolla development stage 7, the tooth already has eruptive force 25 , and the dental element in question was at a more advanced stage.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In cases of delay in the eruption of a dental element, clinical and complementary examinations must be carried out carefully to plan and perform the treatment efficiently 26 . In the present study, ulectomy in the region of tooth #21 was indicated, considering that from the Nolla development stage 7, the tooth already has eruptive force 25 , and the dental element in question was at a more advanced stage.…”
Section: Discussionmentioning
confidence: 98%
“…However, the patient only returned for care after 4 months, when the evolution of root resorption and the presence of dental mobility was observed in tooth #51 (Figure 2A), being exodontics of tooth # 51 indicated (Figure 2B). In the following appointment, upper arch impression taking was performed to make the prosthetic device of functional esthetic Nance arch device with tube-bar system 24 , with the objective of filling the space of the region of the absent anterior teeth, since its permanent successors were in stage 6 of Nolla root development (complete crown formation) 25 (Figure 3A). Orthodontic bands were previously selected for the upper deciduous second molars (Morelli, Sorocaba, SP, Brazil).…”
Section: Report Of the Case Developmentmentioning
confidence: 99%
“…However, the previous report of a supernumerary tooth, in the region of the impacted tooth, may have been associated as a relevant condition for the delayed tooth eruption observed. [11][12][13][14] The surgical technique of the ulectomy is configured by elliptical, circular or oval incisions that delimit the area for tissue excision. Its extension should allow exposure of the incisal edge or occlusal face of the tooth.…”
Section: Discussionmentioning
confidence: 99%
“…Tal procedimento consiste na exérese dos tecidos que revestem a face incisal ou oclusal da coroa, os quais estão interrompendo o processo de erupção, logo, tem como principal função permitir que o dente ocupe sua posição correta na arcada dentária evitando assim cistos, hematomas de erupção e pericoronarite. 16,17 Atualmente, possui dois tipos de procedimentos para essa mesma abordagem sendo eles a ulectomia já caracterizada acima e a ulotomia, onde não há a extração de parte do tecido gengival e consiste em uma incisão simples na gengiva. 18 Entretanto, uma correta indicação de ulectomia só pode ser considerada eficaz e precisa se realizado, com antecedência, exames clínicos e radiográficos.…”
Section: Introductionunclassified